PEMANFAATAN MEDIA DIGITAL DI KALANGAN MAHASISWA PRODI ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS MALIKUSSALEH - Hidayati, Maulia (Universitas Gajah Putih, 2023)
The utilization of digital media has become increasingly widespread among students nowadays no exception students of communication sciences malikussaleh university. Digital media such as the internet, social media, and mobile applications have become integral parts of students' daily lives. This research aims to investigate how students of communication sciences utilize digital media in the contexts of education, communication, and social activities. The research method employed is an online survey involving student respondents from various disciplines. The collected data are analyzed using qualitative and quantitative approaches. The results of this study indicate that students of communication sciences malikussaleh university use digital media to acquire information, communicate with peers and professors, and stay updated with the latest developments in their fields of study. Digital media is also utilized as an additional learning tool and a platform for collaborative group projects. However, there are also some negative impacts of digital media utilization, such as concentration disruptions and addiction. This study provides a better understanding of how students utilize digital media, thereby offering guidance and recommendations for educational institutions to optimize the use of digital media in an academic context.